Perkawinan Sesama Jenis Perspektif Hukum Indonesia dan Hukum Thailand - Difa Fibra Aisyah; Muhammad Teguh Syuhada (CV Rewang Rencang, 2023)
This research aims to discuss comparative laws regarding same-sex marriage in Indonesia and Thailand, with a focus on legal policy, social implications, and impact on generations. This research uses normative legal methods using secondary data sources originating from library materials and legislation. The research results show that Thailand, which is a country that tends to be progressive in recognizing LGBT rights, has initiated legislative steps that provide legal protection for same-sex couples, including the